REACTION OF RAT HEPATOCYTES DURING CORRECTION OF ACUTE EXPERIMENTAL ASEPTIC INFLAMMATION OF THE PERITONEUM BY THE ADMINISTRATION OF CRYOPRESERVED PLACENTA - Voloshyna, O.V.; Shepitko, V.I.; Pelipenko, L.B.; Raskaley, V.B. (World of Medicine and Biology, 2022)
The study of the morphometric parameters of rat hepatocytes during the correction of acute experimental aseptic inflammation of the peritoneum was performed by the injection of cryopreserved placenta. It was found that starting from the 10th day of the experiment, the mean values of hepatocytes’ large and small diameters, as well as the cell area, tended to increase. The value of the nuclear-cytoplasmic index from the 2nd to the 14th day of the experiment was higher than in the intact group. In the study of the size of hepatocytes’ nuclei from the 3rd–5th day of the experiment, a gradual increase in their large and small diameters was noted, which reached maximum values on the 7th and 10th days. Analysis of morphometric parameters proves the efficacy of cryopreserved placenta in the treatment of inflammatory processes.